Pengaruh Pemberian Pestisida Nabati pada Tanaman Bawang Merah (Allium Ascalonicum L.) Terhadap Keanekargaman Anthropoda di Dalam Tanah Lahan Gambut - Soedijo, Samharinto; Aulia Ghanisa, Puspa; Salamiah, Salamiah (Rawa Sains: Jurnal Sains STIPER Amuntai, 2022)
Shallots are one of the most important commodities in the market and they are easily damaged/rotten. This is due to several factors, including natural factors that often occur and cannot be predicted. One of these natural factors is plant-disturbing organisms. Some of them belong to the phylum Arthropods. This study aims to determine the effect of giving some botanical pesticides on shallots to the diversity of arthropods in the soil in peatlands and to determine the abundance of arthropods. This study used a one-factor Randomized Block Design (RBD) consisting of five treatments, namely without pesticides, chemical pesticides, kirinyuh leaf extracts, kepayang seed extracts and galam leaf extracts with four replications, so that there were 20 experimental units. The parameters observed were arthropod type and abundance. There was an effect of giving botanical insecticides on the diversity of arthropods and the evenness of arthropod species in shallot plants on peatlands. The highest diversity was in the control treatment (1.49) and the lowest diversity was in galam leaf extract (0.96). The highest abundance of arthropods was in the group of arthropods of the scavenger type, which indeed dominated the soil by 86.67%.